Case report: Peripheral nerve stimulation relieves post-traumatic trigeminal neuropathic pain and secondary hemifacial dystonia - Li, Junchi; Li, Yongjie; Shu, Wei (Frontiers in Neurology, 2023)
Post-traumatic trigeminal neuropathic pain (PTNP) combined with secondary dystonia are rare sequelae of orofacial injury and often do not respond to conservative treatment. The consensus on treatment for both symptoms has yet to be standardized. We report a 57-year-old male patient with left orbital trauma who developed PTNP immediately after the injury and secondary hemifacial dystonia 7 months thereafter. To treat this condition, we performed peripheral nerve stimulation (PNS) using a percutaneously implanted electrode to the ipsilateral supraorbital notch along the brow arch, instantly resolving his pain and dystonia. PTNP was relieved satisfactorily until last follow-up, despite the dystonia gradually recurred 6 months after surgery. To our knowledge, this is the first reported case of PNS used for the treatment of a patient with PTNP combined with dystonia. This case report highlights the potential benefits of PNS in relieving neuropathic pain and dystonia, and discusses its therapeutic mechanism. Moreover, this report suggests that secondary dystonia may occur due to the uncoordinated integration of afferent sensory and efferent motor information. We believe that PNS should be considered for patients with PTNP following the failure of conservative treatment. Secondary hemifacial dystonia may benefit from PNS, upon further research and long-term assessment.